2014
DOI: 10.1094/phyto-10-13-0271-r
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Predominance of a Small Number of Genotypes in Greenhouse Populations of Botrytis cinerea

Abstract: Although Botrytis cinerea is known for its ability to produce high amounts of spores on diseased plants, enabling it to complete rapidly numerous developmental cycles in favorable environments, population genetics studies of this fungus indicate enormous diversity and limited clonal spread. Here, we report an exception to this situation in the settings of commercial tomato greenhouses. The genotypic characterization of 712 isolates collected from the air and from diseased plants, following the development of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…On tomato plants, B. cinerea sporulates on leaves, stems or fruits and the spores are easily disseminated by air currents and by the frequent technical interventions necessitated by this crop. As this often coincides with favourable microclimatic conditions for disease development, this allows for successive cycles of inoculum production to occur in the greenhouse (Dik & Wubben, ; Decognet et al ., ; Bardin et al ., ). Indeed, in the experimental greenhouse in the present study, sporulating lesions were observed on aerial parts of about 11% of tomato plants during the growing period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On tomato plants, B. cinerea sporulates on leaves, stems or fruits and the spores are easily disseminated by air currents and by the frequent technical interventions necessitated by this crop. As this often coincides with favourable microclimatic conditions for disease development, this allows for successive cycles of inoculum production to occur in the greenhouse (Dik & Wubben, ; Decognet et al ., ; Bardin et al ., ). Indeed, in the experimental greenhouse in the present study, sporulating lesions were observed on aerial parts of about 11% of tomato plants during the growing period.…”
Section: Discussionmentioning
confidence: 99%
“…Both lettuce and tomato plants are likely to have been exposed to airborne inoculum entering from outside the greenhouse. Exchange of air between the inside and the outside of a greenhouse can occur regularly through vents (Leyronas et al, 2011), and Bardin et al (2014) have recently shown that the contribution of external inoculum was non-negligible. In addition to airborne inoculum, the plants may have been confronted with soilborne inoculum, with a greater impact on lettuce whose foliage quickly covers the soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the array of molecular techniques and computing technologies, offers endless possibilities of conducting mark-release-recapture experiments that allow tracking of inoculum sources during disease development and thus determines the inoculum origin (Bardin et al 2014;Sommerhalder et al 2010;Zhan et al 1998;Zhan and McDonald 2013). Mark-release-recapture experiments have been reported for the wheat pathogen Phaeosphaeria nodorum (Bennet et al 2007;Shah et al 1995) and other pathogens (Zhan and McDonald 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of correlation between the abundance of soilborne inoculum before the planting of the lettuce crop and the incidence of grey mould at harvest suggests that other sources of inoculum may also have contributed to the epidemics in the two greenhouses. Air is one probable additional source of inoculum as it has been shown that exchange of inoculum can occur between the inside and the outside of a greenhouse through vents (Korolev et al ., ; Leyronas et al ., ; Bardin et al ., ). The airborne conidia deposited in the tunnels may have been collected by the mulch covering the soil and carried by sprinkler irrigation water to zones that retain humidity, such as the collar area of the plants and the underside of the basal leaves.…”
Section: Discussionmentioning
confidence: 97%